YouTube as an information source for instrument separation in root canal treatment - Yağız Özbay; Neslihan Yılmaz Çırakoğlu (Restorative Dentistry & Endodontics)
ObjectivesThe reliability and educational quality of videos on YouTube for patients seeking information regarding instrument separation in root canal treatment were evaluated.Materials and MethodsYouTube was searched for videos on instrument separation in root canal treatment. Video content was scored based on reliability in terms of 3 categories (etiology, procedure, and prognosis) and based on video flow, quality, and educational usefulness using the Global Quality Score (GQS). Descriptive statistics were obtained and the data were analyzed using analysis of variance and the Kruskal-Wallis test.ResultsThe highest mean completeness scores were obtained for videos published by dentists or specialists (1.48 ± 1.06). There was no statistically significant difference among sources of upload in terms of content completeness. The highest mean GQS was found for videos published by dentists or specialists (1.82 ± 0.96), although there was no statistically significant correlation between GQS and the source of upload.ConclusionsVideos on YouTube have incomplete and low-quality content for patients who are concerned about instrument separation during endodontic treatment, or who experience this complication during endodontic treatment.